Resisted sprint velocity in female soccer players: Influence of physical capacities - Loturco, I.; Jeffreys, I.; Kobal, R.; Reis, V. P.; Fernandes, V.; Rossetti, M.; Pereira, L. A.; McGuigan, M. (International Journal of Sports Medicine, 2020)
This study aimed to examine the effects of different sled overloads on maximum sprint velocity achieved by female soccer players with different strength, speed, and power levels. Twenty elite female soccer players from the same club participated. On the same day, athletes performed: linear and resisted-sprint tests with 30 and 60 % of body-mass over 5-, 10-, and 20-m; half-squat maximum bar-power output, and half-squat one-repetition maximum assessment. A median split analysis was used to divide players into two groups according to their velocity, half-squat one-repetition maximum, and half-squat power. Differences in percentage decreases between unresisted- and resisted-sprints comparing higher and lower groups were analyzed using magnitude-based inferences. Overall, the stronger, faster, and more powerful players were less affected by both loads, as demonstrated by their lower decreases in velocity over the different distances. However, half-squat power appeared to be more sensitive for indicating impairments in resisted-sprint performance, due to meaningful differences in percentage decreases observed between higher and lower power groups. Notably, overloads of 30 and 60% of body-mass provoked substantial reductions in resisted-sprint velocity (~22.9% for 30% and ~51.4% for 60% of body-mass, relative to unresisted-sprint velocity). Athletes with superior power levels are less affected by the progressive sled overloading.